Experimental investigation on rheological, momentum and heat transfer characteristics of flowing fiber crop suspensions. (January 2017) - Gharehkhani, Samira; Yarmand, Hooman; Goodarzi, Mohammad Shahab; Shirazi, Seyed Farid Seyed; Amiri, Ahmad; Zubir, Mohd Nashrul Mohd; Solangi, Khalid; Ibrahim, Rushdan; Kazi, Salim Newaz; Wongwises, Somchai
Abstract: The study of pulp suspension flow is one of the most significant scientific interests since the considerable changes in the flow behavior of water were noticed after adding a small amount of fiber to water. The rheological studies on Kenaf pulp (a fiber crop) suspensions revealed that concentration has a great influence on variations of viscosity and yielded stress values. Heat transfer and pressure loss data were obtained from Kenaf suspension flow at different concentrations over a wide velocity range in a straight pipe. Kenaf suspension at the concentration of 0.6 wt.% showed maximum drag reduction. A considerable increase in the heat transfer coefficient of Kenaf suspension (0.2 wt.%) was also observed. Such an increment in the heat transfer coefficient ratio of Kenaf suspension flow is interesting since the enhancement of heat transfer has mostly been reported for suspensions containing nanoparticles and not for natural fibers in microscale. Moreover, the effects of fiber length and flexibility on momentum and heat transfer data were studied.